Multiband Printed Asymmetric Dipole Antenna for LTE/WLAN Applications - Chia-Mei Peng; I-Fong Chen; Chin-Hao Liu (International Journal of Antennas and Propagation)
The ability of a single layer strip fed printed asymmetric dipole antenna, which is composed of top-loading, asymmetric coplanar waveguide (ACPW) and stepped-feeding structure, to operate at three wide frequency bands (698~960 MHz, 1710~2620 MHz, and 5150~5850 MHz) to cover WLAN and LTE operation has been demonstrated. A prototype of the proposed antenna with 57.5 mm in length, 0.4 mm in thickness, and 5 mm in width is fabricated and experimentally investigated. The experimental results indicate that the VSWR 2.5 : 1 bandwidths achieved were 74.3%, 40.8%, and 18.2% at 700 MHz, 2450 MHz, and 5500 MHz, respectively. Experimental results are shown to verify the validity of theoretical work.